Design, synthesis and evaluation of 2, 6, 8-substituted Imidazopyridine derivatives as potent PI3Kα inhibitors - Rui Chen; Zhongyuan Wang; Lijie Sima; Hu Cheng; Bilan Luo; Jianta Wang; Bing Guo; Shunyi Mao; Zhixu Zhou; Jingang Peng; Lei Tang; Xinfu Liu; et al. (Taylor & Francis Group, 2023)
Inhibition of PI3K pathway has become a desirable strategy for cancer treatment. In this work, a series of 2, 6, 8-substituted Imidazo[1,2-a]pyridine derivatives were designed and screened for their activities against PI3Kα and a panel of PI3Kα-addicted cancer cells. Among them, compound 35 was identified as a PI3Kα inhibitor with nanomolar potency as well as acceptable antiproliferative activity. Flow cytometry analysis confirmed 35 induced cell cycle arrest and apoptosis in T47D cells. In addition, it also showed desirable in vitro ADME properties. The design, synthesis, and SAR exploration of 35 are described within.